Scoliosis and anaesthetic considerations - Anand H Kulkarni; M Ambareesha (Indian Journal of Anaesthesia, 2007)
Scoliosis may be of varied etiology and tends to cause a restrictive ventilatory defect, along with ventilation-perfusion mismatch and hypoxemia. There is also cardiovascular involvement in the form of raised right heart pressures, mitral valve prolapse or congenital heart disease. Thus a careful pre-anaesthetic evaluation and optimization should be done. Intraoperatively temperature and fluid balance, positioning, spinal cord integrity testing and blood conservation techniques are to be kept in mind. Postoperatively, intensive respiratory therapy and pain management are prime concerns.